2013
DOI: 10.1098/rspb.2013.0847
|View full text |Cite
|
Sign up to set email alerts
|

Variation in breeding phenology provides insights into drivers of long-term population change in harbour seals

Abstract: Phenological trends provide important indicators of environmental change and population dynamics. However, the use of untested population-level measures can lead to incorrect conclusions about phenological trends, particularly when changes in population structure or density are ignored. We used individual-based estimates of birth date and lactation duration of harbour seals (Phoca vitulina) to investigate energetic consequences of changes in pupping phenology. Using generalized linear mixed models, we first de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 49 publications
4
39
1
Order By: Relevance
“…Our findings add to a small but growing number of large‐mammal studies reporting repeatability of birth dates for individuals (Lunn and Boyd ; Boyd ; Ellis et al. ; Cordes and Thompson ; Plard et al. , ; Wolcott et al.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Our findings add to a small but growing number of large‐mammal studies reporting repeatability of birth dates for individuals (Lunn and Boyd ; Boyd ; Ellis et al. ; Cordes and Thompson ; Plard et al. , ; Wolcott et al.…”
Section: Discussionsupporting
confidence: 58%
“…). Even after such factors are considered, some individuals repeatedly give birth earlier or later than others (Cordes and Thompson ; Plard et al. ; Wolcott et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), and declining populations were associated with either later mean parturition dates when subject to bottom‐up control (Bowen et al . ) or earlier mean parturition dates when subject to top‐down control (Cordes and Thompson ).…”
Section: Model Selection Results For Fixed Effects Of Maternal Age Onmentioning
confidence: 99%
“…Interestingly, despite large fluctuations in the population size during this time, due to a combination of factors (Matthiopoulos et al, 2014;Thompson, Mackey, Barton, Duck, & Butler, 2007), the length-at-age data did not show any substantial or biologically significant variation in the residuals around the growth function over time. Similarly, Cordes and Thompson (2013) concluded that an advance in pupping date during a period of decline was likely to be related to top-down (direct removals) rather than bottom-up processes. Similarly, Cordes and Thompson (2013) concluded that an advance in pupping date during a period of decline was likely to be related to top-down (direct removals) rather than bottom-up processes.…”
Section: Discussionmentioning
confidence: 99%